2015
DOI: 10.1186/s12912-015-0081-y
|View full text |Cite
|
Sign up to set email alerts
|

Career development expectations and challenges of midwives in Urban Tanzania: a preliminary study

Abstract: BackgroundApproaches to addressing the shortage of midwives are a great need especially in Sub-Saharan Africa including Tanzania. The midwifery shortage in Tanzania consists of two major causes; the first is the shortage of pre-service nursing training and the second is the low rate of retention as it is difficult to sustain midwives’ career motivations. Lack of opportunities for career development, is one of the most related problems to keep midwives motivated. Continuing education as an approach to career de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…Similar to Tanaka et al. (), our study reinforces the midwives’ and obstetricians’ desire to share their knowledge and information with mothers, particularly in relation to danger signs, how to care for the baby and the management of nutrition.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to Tanaka et al. (), our study reinforces the midwives’ and obstetricians’ desire to share their knowledge and information with mothers, particularly in relation to danger signs, how to care for the baby and the management of nutrition.…”
Section: Discussionsupporting
confidence: 89%
“…The nurse‐midwives’ and obstetricians’ commitments, moral beliefs, their values towards the mothers and babies were strong driving forces to providing the best care possible to the mothers and babies regardless of the frustrating conditions they sometimes encountered. Tanaka, Horiuchi, Shimpuku, and Leshabari () also found that midwives were eager to increase their knowledge to reduce neonatal mortality and improve maternal health outcomes. Similar to Tanaka et al.…”
Section: Discussionmentioning
confidence: 98%
“…Continued education is one of the most effective ways to heighten midwives’ motivation and cultivate midwives’ skills [22]. Skilled and motivated midwives with possibilities for career development has proven to be an efficient way to reduce mother and child mortality [5].…”
Section: Discussionmentioning
confidence: 99%
“…The current definition of CPD varies country by country and, in some countries it is used synonymously with continuing nursing education, continuing medical education, short courses, in-service training, lifelong learning, as well as other terms (African Regulatory Collaborative, 2013). In-service training programs can be important tools in health workforce retention, such as with midwives in Tanzania (Tanaka, Horiuchi, Shimpuku, & Leshabari, 2015), can be used to strengthen service delivery as demonstrated with health workers in Rwanda (Cancedda, Farmer, Kyamanywa, & Riviello, 2014), and is an effective way to improve knowledge and confidence as seen with skilled birth attendants in Malawi and India (Evans et al, 2014). Given the numerous benefits, there is a growing international trend to require and regulate CPD completion for nursing and midwifery re-licensure (African Regulatory Collaborative, 2013).…”
mentioning
confidence: 99%
“…However, despite increasing CPD requirements, nurses commonly face barriers to accessing CPD (Richards, & Potgieter, 2010; Tanaka et al, 2015). Due to workforce shortages, high volume patient loads, limited resources, and strained training facilities, as well as great distances to access in-person CPD trainings, nurses and midwives frequently lack opportunities to attend facilitated CPD trainings (African Regulatory Collaborative, 2013).…”
mentioning
confidence: 99%